2020
DOI: 10.1002/ptr.6657
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive review on ethnomedicine, phytochemistry, pharmacology, and toxicity of Tephrosia purpurea (L.) Pers.

Abstract: Tephrosia purpurea (L.) Pers. is a well‐known plant in Ayurveda and named “Sarwa wranvishapaka” for its property to heal wounds. Traditionally, it is practiced for impotency, asthma, dyspepsia, hemorrhoids, syphilis gonorrhea, rheumatism, enlargement of kidney and spleen. It is an important component of herbal preparations like Tephroli and Yakrifti used to cure liver disorders. Various phytocompounds including pongamol, purpurin, purpurenone, tephrosin, bulnesol, tephrostachin, β‐sitosterol, and so on have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 101 publications
1
9
0
Order By: Relevance
“…This is not a good sign for the young generation because, in time to come, their unique traditional knowledge may become extinct, and this is also mentioned in similar studies conducted in other parts [80][81][82]. Further, Rao et al [83] believed that the education of the informants in Kathua district and adjoining areas negatively correlated with knowledge; education increases the knowledge of modern sciences, and slowly and steadily decreases the indigenous practice of culture and the use of herbal plants. Bhatia et al [84] and Singh et al [85] suggested that the reason for the continuously declining indigenous medicinal plant use knowledge could be that, in order to acquire education, the younger generation moves away from their residence; after getting an education, they look for employment in cities/towns, and as time passes, they get more exposed to modernization, which could include more education, high-quality occupation, and the habit of consumerism.…”
Section: Characteristics Of Informantsmentioning
confidence: 96%
See 2 more Smart Citations
“…This is not a good sign for the young generation because, in time to come, their unique traditional knowledge may become extinct, and this is also mentioned in similar studies conducted in other parts [80][81][82]. Further, Rao et al [83] believed that the education of the informants in Kathua district and adjoining areas negatively correlated with knowledge; education increases the knowledge of modern sciences, and slowly and steadily decreases the indigenous practice of culture and the use of herbal plants. Bhatia et al [84] and Singh et al [85] suggested that the reason for the continuously declining indigenous medicinal plant use knowledge could be that, in order to acquire education, the younger generation moves away from their residence; after getting an education, they look for employment in cities/towns, and as time passes, they get more exposed to modernization, which could include more education, high-quality occupation, and the habit of consumerism.…”
Section: Characteristics Of Informantsmentioning
confidence: 96%
“…For each recorded species from the JWS, we provided the scientific (botanical) name, family, voucher specimen number, local (Dogri) name, life-form (tree, shrub, herb, liana), part (s) used (whole plant, bark, root, rhizome, seed, leaves, flower, fruit, latex, resin), ailments treated (disease category), mode of usage (paste, decoction, oral, chewed, powder, juice), use-value, and relative importance (Table 4). Fabaceae, Asteraceae, Euphorbiaceae, Apocynaceae, Lamiaceae, Rosaceae, Convolvulaceae, and Solanaceae are the most commonly used ethnomedicinal plant families in the Himalayas, and Rao et al [83] are of the opinion that the reason could be that the plants of these families were well-known among the hilly indigenous communities for their active chemical constituents and easy availability in all climatic conditions. In line with this view, various pharmacopeia also mentioned the importance of these families among the local people, and the reason for this could be that these plant species are a rich source of alkaloids and flavonoids needed for growth and as building blocks of the body [1,57].…”
Section: Floristic Analysis Offamilies Of Medicinal Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thanks to its soft texture, suitable for all skin types (very dry, dry, normal, mixed, oily, impure, mature, or sensitive), the cream is rapidly absorbed, leaving a soft, smooth, and radiant skin face [129]. GIVAUDAN performed a specific extraction process for obtaining a concentrated extract enriched in specific sugars, including stachyose and ciceritol, from the seeds of Tephrosia purpurea [89,130,131], creating Neurophroline™ [78]; it is designed to combat the multiple stress source effects present daily [56,130,132]. In detail, Neurophroline™ works to reduce the production of cortisol by skin cells (−70% within 2 h, in vitro) and to stimulate the release of β-endorphins (+163% within 24 h, in vitro).…”
Section: Discovering Neurocosmetic Ingredients From Plant Extractsmentioning
confidence: 99%
“…Phytosterols are kinds of active ingredients in plant cell membrane which are structurally similar with animal sterol, such as cholesterol. Dandelion β-sitosterol belongs to phytosterols and plays significant roles in antagonizing cancers [63] . Previous studies had proved sitosterol inhibited lung cancer A549 and NCI-H460 cells growth through a dose-dependent manner and blocked cell cycle in G 2 / M phase [64][65][66] .…”
Section: β-Sitosterolmentioning
confidence: 99%